IMPLEMENTASI KEBIJAKAN GERBANG EMAS BERSINAR DALAM MENGUKUR IPM DI KABUPATEN TABALONG - Anang Syakhfiani; Sampara Lukman; Khasan Effendy; Marja Sinurat (GoAcademica Research dan Publishing, 2020)
In the last ten years the Human Development Index (HDI) in Tabalong Regency, South Kalimantan Province has always been at the bottom of all regencies/cities, namely between 9th and 10th, this is very sad because it is contrary to the condition of Tabalong District which is rich in Natural Resource. In connection with this the local government is trying to find ways to improve HDI so that it can catch up with other regions. Gerbang Emas Bersinar Program, which began in 2015 by local governments targeting mainly in the fields of economy, health education and people's welfare, was able to improve the HDI of Tabalong Regency, which had always been ranked lower in the last few years, always in the top 5. This research will explain how tGerbang Emas Bersinar Policy can contribute to the improvement of HDI in Tabalong Regency.